#TITLE_ALTERNATIVE# - HAMAMA (NIM 10704076), NADIA
Galendo, the edible by product of coconut oil production, contains relatively high amount of protein, but commercial galendo still contains relatively high amount of oil causing galendo to be readily rancid and sticky. Reduction of oil content of the galendo would reduce the rate of becoming rancid and would make it more practical to be processed. Oil content of galendo was reduced by reflux method with ethyl acetate. Before and after extraction process, the oil content was determined by Weibull method of extraction, the protein content by Kjeldahl, the carbohydrate content by colorimetry, water content, loss on drying, residue of ignition, heavy metal content, acrylamide content, peroxide values, and flow rate of the galendo powder were determined. Galendo after extraction had total oil 0.03+-0.01%, protein 42.1+-0.9%, carbohydrate 45.1+-0.2%, water content 2.9%, loss on drying 3%, residue of ignition 8.1%, heavy metal less than 1 ppm, acrylamide 0.07 ppm, and peroxide value not detected after 90 days storage. After extraction, the galendo of very low oil content (less than 0.05%) was unsticky, not readily rancid, and after being powdered, it was able to flow freely with a flow rate more than 4 g/second.